Towards a cost-based design of heaving point absorbers. (June 2017) - Piscopo, V.; Benassai, G.; Della Morte, R.; Scamardella, A.
Highlights: Cost-based optimization of heaving point absorber hydrodynamic performances by phase control under several motion restraint conditions. Incidence of floating buoy dimensions, fully submerged mass and PTO damping on device yearly energy efficiency. Detection of minimum cost configuration by the Levelised Cost of Energy and the Annual Energy Production per unit area. Parametric analysis at five candidate deployment sites located in the Mediterranean Sea and in the Atlantic Ocean. Abstract: The need for increasing the share of sea resources in the global renewable energy market requires a specialized design of wave energy converters and Power Take-Off units that, in turn, may be capable of maximising power production and minimizing extraction costs. In this respect, as optimization of wave energy converter performances, by properly tuning relevant hydrodynamic parameters and controlling the motion in waves, reveals a basic issue to reduce energy production charges, a new cost-based design procedure for heaving point absorber type devices is developed, with the main aim of accounting for wave climate at deployment site, reliable device operational profiles and design restraint criteria for both floating buoy and Power Take-Off unit. The newly proposed cost-based procedure is applied to detect the optimum configuration of heaving point absorber devices at several candidate deployment sites. Finally, the incidence of wave climate and available energy resources, on detecting the optimum device configuration and assessing relevant energy production costs, is investigated and fully discussed.